(untitled) (Victoria Journal of Management, 2025)
This paper examines the gender issues in human resource management in Nepalese economic sector. The Study observes that the government has not pursued an employment policy that promotes gender balance. Despite of various constitutional and other measures been introduced to address marginalization and discrimination against women, evidence presented in this paper shows that women still continue to face these issues. This paper also focuses that most of the women working in different sectors hold lower-level positions and also do not have easy access to the skills, training and resources which is needed for better and more stable jobs. Data were obtained from government websites mainly of public service commission, central bureau of statistics, Nepal Rastra Bank and Nepal Census-2021 online report. Beside these, articles of different scholars related to human resource management were reviewed too. Over the past 9 years, women’s access to literacy, health and education has been increased; inequalities between men and women, ethnic groups and castes have still remained. Thus, the result has been clearly noticed in different sectors in the Nepalese economy and many more. The paper shows that in recent year’s women participation in different sectors has been increased. Mainly in the politics women participation has been great but in other economic sectors and in public service of Nepal it is still very low. This paper argues that, equal opportunity is not enough; affirmative action is needed to make it a reality for minorities and women. It also concludes that different government institutions must create policies to ensure the equal opportunities for women to contribute for national development.